Thermally Stabilized Rigid Polyurethane Composite Foams With Green-Synthesized Lignin Nanoparticles for Structural Panel Applications - Kaya, Ali Ihsan; Yalcin, Omer Umit; Gulsoy, Sezgin Koray; Aydemir, Deniz (Wiley, 2026)
This study examined the feasibility of using lignin nanoparticles (L) produced with a deep eutectic solvent (DES) at loadings of 5, 10, and 20 wt% as a sustainable alternative to synthetic components in rigid polyurethane (rPU) composite blends. The resulting composite foams were characterized for physical, morphological, thermal, structural, and mechanical properties. The results demonstrated that incorporating L significantly enhanced the volumetric expansion of the foams and simultaneously reduced their density, indicating improved foaming efficiency. However, water absorption increased with higher L content, attributed to residual hydrophilic groups in the lignin structure. SEM observations revealed that foams containing 5 wt% L exhibited a more homogeneous, uniform cell morphology. In contrast, higher L loadings led to cell coalescence, irregular cell structures, and nanoparticle agglomeration, adversely affecting structural integrity. XRD analysis showed a pronounced increase in the amorphous character of the foams, with crystallinity decreasing from 45.6% in neat rPU to 35.2% at 20 wt% L content. Thermal analyses indicated improved thermal stability and enhanced flame resistance, likely due to the formation of a protective char layer during degradation. Although mechanical properties decreased with increasing L content, the thermal insulation performance of the foams improved, as evidenced by lower thermal conductivities.
Keywords: Deep Eutectic Solvents; Forest-Based Raw Materials; Nano Lignin; Rigid Polyurethane